Clinical legal education initiatives in The International Islamic University Malaysia - Maidin, Ainul Jaria (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
This paper seeks to set out the initiative proposed to be taken by the International Islamic University Malaysia in introducing the clinical legal education program for the law undergraduates. The paper will briefly set out the background information on the need to address the weaknesses in the law teaching methods reason and the need to introduce clinical legal education into the law-teaching curriculum. This is followed by a brief overview of the benefits of the clinical legal education and how the students from the faculty of law of the International Islamic University Malaysia can benefit from such program. Finally, the paper will endeavour to identify the possible constraints and suggest ways to overcome such constraints in the process of introducing and implementing the Clinical Legal Education (CLE) programme.